Planning an artificial intelligence diabetic retinopathy screening program: a human-centered design approach - Scanzera, Angelica C.; Beversluis, Cameron; Potharazu, Archit V.; Bai, Patricia; Leifer, Ariel; Cole, Emily; Du, David Yuzhou; Musick, Hugh; Chan, R. V. Paul (Frontiers in Medicine, 2023)
Diabetic retinopathy (DR) is a leading cause of vision loss in the United States and throughout the world. With early detection and treatment, sight-threatening sequelae from DR can be prevented.Although artificial intelligence (AI) based DR screening programs have been proven to be effective in identifying patients at high risk of vision loss, adoption of AI in clinical practice has been slow. We adapted the United Kingdom Design Council's Double-Diamond model to design a strategy for care delivery which integrates an AI-based screening program for DR into a primary care setting.Methods from human-centered design were used to develop a strategy for implementation informed by context-specific barriers and facilitators. The purpose of this community case study is to present findings from this work in progress, including a system of protocols, educational documents and workflows created using key stakeholder input.